Choi-Davis-Jensen Inequalities in Semifinite von Neumann Algebras - Turdebek N. Bekjan; Kordan N. Ospanov; Asilbek Zulkhazhav (Journal of Function Spaces)
We prove the Choi-Davis-Jensen type submajorization inequalities on semifinite von Neumann algebras for concave functions and convex functions.